Coiling of shaft of the central venous catheter inside left subclavian vein- a case report - Rajbanshi, Lalit Kumar; Karki, Shambhu Bahadur; Arjyal, Batsalya (Journal of Society of Anesthesiologists of Nepal, 2018)
Central venous catheterization is one of the common procedures used for gaining vascular access for various indications. Sometimes, the catheter can take unusual course inside the vein that can lead to erroneous pressure measurement, increase the risk of thrombosis or trauma to the vessel. Any resistance during insertion of the guide wire or catheter and absence of blood aspiration are some alarming signs that help to detect malposition at the earliest moment. We report a case of coiling of the shaft of the central venous catheter inside left sublacvian vein in a patient with head injury. Technical expertise, sound knowledge of anatomical landmarks and use of real time ultrasound can minimize malposition of the catheter. We suggest at any moment if there is resistance during insertion of guide wire or catheter or if there is absence of blood aspiration from any of the lumen, the catheter should be removed immediately suspecting malposition. Journal of Society of Anesthesiologists of Nepal Vol. 4, No. 2, 2017, page: 87-90